You Can't Make Me Do It: State Implementation of Insurance Exchanges under the Affordable Care Act. (3rd May 2013) - Haeder, Simon F.; Weimer, David L.
<x xml:space="preserve">Abstract</x> The Patient Protection and Affordable Care Act (ACA) of 2010 has been one of the most controversial laws in decades. The ACA relies extensively on the cooperation of states for its implementation, offering opportunities for both local adaptation and political roadblocks. Health insurance exchanges are one of the most important components of the ACA for achieving its goal of near‐universal coverage. Despite significant financial support from the federal government, many governors and legislatures have taken actions that have blocked or delayed significant progress in developing their exchanges. However, many state commissioners of insurance have played constructive roles in moving states forward in exchange planning through their expertise, leadership, and pragmatism, sometimes in spite of strong political opposition to the ACA from governors and legislatures.